The Influence of School Leadership and Committee Performance on Improving the Quality of Learning Islamic Education - Kamsia Nur’aini; Ahmad Syahid; Rustina Rustina (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2020)
This study aims to determine the effect of school committee performance on improving the quality of educational learning and principal leadership on Islamic learning. This study uses quantitative methods because the research data is in the form of numbers and the analysis uses statistics. The variables in this study are the contribution of the school committee's performance, the leadership of the school principal and the improvement of the quality of learning Islamic religious education. The data were processed using SPSS version 21. The results showed that there was a significant influence between the performance of the school committee and the improvement of the learning quality of Islamic religious education by 37.8% and the remaining 62.2% was influenced by other factors outside the research. This data shows that the higher the influence of the school committee's performance, the higher the increase in the quality of learning. In other words, the school committee is an institution that is located in each educational unit, and is an independent body that does not have a hierarchical relationship with government institutions that are in the middle between parents, students, teachers, and the local community. Furthermore, there is the influence of the principal's leadership on improving the quality of Islamic religious education learning by 66.4% and the difference of 33.6% is influenced by other factors outside the research. This data shows that the higher the influence of the principal's leadership, the higher the increase in the quality of learning.